ANALISIS IMPLEMENTASI SIKAP DALAM KURIKULUM 2013 PADA PEMBELAJARAN BIOLOGI DI SMA - Anggraeni, Ika; Rahmi, Ennike Gusti; Sefrinal, Sefrinal (Jurnal Manajemen Pendidikan, 2021)
The main objective of the 2013 Curriculum is the formation of student character. The character of students is inseparable from the development of students' attitudes themselves. The development and formation of student attitudes can be done through direct learning and indirect learning. This study aims to look at the content of attitudes in lesson plans and the implementation of attitudes in biology learning. The research method used in this research is descriptive method. The research sample was determined by purposive sampling technique. Data were obtained through documentation studies, learning observations, and student statement questionnaires. This research was conducted at the Piloting High School Curriculum 2013 Cluster three in the city of Bandung. The results showed that in general the content of attitude competence in the lesson plan was 48.21% with the less category. The low content of attitudes in the lesson plans and their implementation has implications for the formation of student attitudes in learning, as seen from the 18 attitudes observed, only five attitudes became student habits. It is feared that this situation will hinder the achievement of the objectives of implementing the 2013 Curriculum and the goals of national education to shape the character of students